ESTIMATING SURFACE VELOCITIES IN THE SOUTHERN BRAZILIAN AND URUGUAYAN CONTINENTAL SHELVES USING THE MAXIMUM CROSS-CORRELATION METHOD - Costi, J.; Kirinus, E. P.; Marques, W. C.; Garcia, C. A. E.; Fujita, C. (Revista de Engenharia Térmica, 2017)
The present study investigates the viability of using the maximum cross- correlation method on ocean color imagery to estimate surface velocities on the Southern Brazilian and Uruguayan continental shelf. The method searches for maximum correlation areas in two sequential images, determining the displacement of oceanographic features within the time interval of the images acquisition. We use the NWL550 parameter of MODIS-Aqua imagery, once it is well correlated with the total suspended matter in the water and provides relatively well-defined optical features on the Southern Brazilian and Uruguayan continental shelves. The estimated velocity fields showed a preferential direction northward, with average intensities between 0.06 m/s and 0.11 m/s. The frequent cloud coverage and the diffusive processes restrict the number of image pairs suitable for the analysis. Nevertheless, the method showed potential for investigating the current velocity fields on the study area, as the estimates are in agreement with the wind fields and the velocities’ intensities are well within the values previously described in the literature for the region.